Religion and Education: A Comparative Analysis of Indonesian and Tunisian Religious Moderation Policies - Husna, Ade; Zuhdi, Muhammad (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2024)
Indonesia and Tunisia offer distinct cultural, political, and educational environments related to religious moderation, despite having predominantly Muslim populations. The two nations' divergent approaches to religion show their attempts to take a moderate stance. Focusing on the dynamics of modern educational standards, the paper examines the nuanced policies employed by the two nations to encourage religious moderation in their educational systems. This study utilized a qualitative method by conducting interviews, literature analysis, and taking a few key points from formal events pertaining to this subject. By contrasting the experiences of Tunisia and Indonesia, this study seeks to clarify the different strategies for promoting religious moderation and fostering a friendly, inclusive learning environment. The main result of this research is that Indonesia inserted religious moderation into its' educational curriculum. Unlike the state policies in Tunisia, which don't make a specific curriculum about religious moderation in the educational aspect but make some conferences and forums related to this issue. The research findings contribute to the global conversation on harmonizing religion and education.